Local Culture-Based Character Education Cultivating Cooperation through Gendang Beleq Schools - Endang, Sri; Bilal, Arpan Islami; Muhdar, Syafruddin (Moestopo International Review on Social, Humanities, and Sciences, 2026)
This study examines the contribution of the Gendang Beleq tradition in promoting mutual cooperation among elementary school students. Previous research has largely focused on Gendang Beleq as a performing art and cultural heritage, with limited attention to its role in character education, particularly in fostering cooperation. This study adopts a qualitative case study approach conducted at SDN Petemon, Lendang Ara Village, Kopang Subdistrict, Lombok. It involves five informants: the school principal, a teacher of Gendang Beleq and Pancasila Education, and three fifth-grade students actively engaged in the activities. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that Gendang Beleq activities provide students with direct experiences of cooperation, shared responsibility, discipline, and social interaction through group practice and performance. Additionally, these activities contribute to preserving local culture while supporting the development of students’ character and social values.